2017
DOI: 10.1111/bcp.13358
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative disease progression model of α‐1 proteinase inhibitor therapy on computed tomography lung density in patients with α‐1 antitrypsin deficiency

Abstract: AimsEarly‐onset emphysema attributed to α‐1 antitrypsin deficiency (AATD) is frequently overlooked and undertreated. RAPID‐RCT/RAPID‐OLE, the largest clinical trials of purified human α‐1 proteinase inhibitor (A1‐PI; 60 mg kg–1 week–1) therapy completed to date, demonstrated for the first time that A1‐PI is clinically effective in slowing lung tissue loss in AATD. A posthoc pharmacometric analysis was undertaken to further explore dose, exposure and response.MethodsA disease progression model was constructed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…Whether the standard recommended dose of 60 mg/kg is most adequate remains unclear, as some patients on the standard dose can still exhibit residual inflammation, protease activity, and elastin degradation which can be further mitigated by increasing the treatment dose. 78 Pharmacometric analysis of data from the RAPID trials has suggested that increasing serum levels above the 11 µM threshold is associated with greater clinical effect; 56,104 a finding that was supported by a recent pilot study, which observed significant improvements in multiple markers of disease activity in patients up-titrated from 60 to 120 mg/kg AAT per week. 78 Increasing the dose to 120 mg/kg per week was also well tolerated and restored serum AAT levels to be more in line with the normal range (>25 µM).…”
Section: What We Do Not Knowmentioning
confidence: 98%
“…Whether the standard recommended dose of 60 mg/kg is most adequate remains unclear, as some patients on the standard dose can still exhibit residual inflammation, protease activity, and elastin degradation which can be further mitigated by increasing the treatment dose. 78 Pharmacometric analysis of data from the RAPID trials has suggested that increasing serum levels above the 11 µM threshold is associated with greater clinical effect; 56,104 a finding that was supported by a recent pilot study, which observed significant improvements in multiple markers of disease activity in patients up-titrated from 60 to 120 mg/kg AAT per week. 78 Increasing the dose to 120 mg/kg per week was also well tolerated and restored serum AAT levels to be more in line with the normal range (>25 µM).…”
Section: What We Do Not Knowmentioning
confidence: 98%
“…27 Tortorici et al, who found that clinical efficacy did not plateau as AAT exposure was increased, suggested that there may be a role for higher AAT doses. 28 The SPARK trial (Safety and Pharmacokinetics of Alpha-1 Proteinase Inhibitor in Subjects with Alpha-1 Antitrypsin Deficiency; ClinicalTrials identifier: NCT01213043) in 2013 found that double-dose 120 mg/kg/week achieved a higher mean steady state serum concentration of 27.7 µM (versus 17.3 µM in the 60 mg/kg/week group) with a similar safety profile. 29 A follow-up pilot study with eight patients with AATD was conducted in 2019, which found that double-dose therapy for 4 weeks significantly reduced serine protease activity in bronchoalveolar lavage fluid (BALF) and plasma, and reduced markers of elastin degradation (desmosine, isodesmosine) in BALF.…”
Section: Established Therapiesmentioning
confidence: 99%
“…Data from population pharmacokinetic simulations predicted that trough levels above the 11 µM protective threshold would be maintained in the majority of patients treated with bi-weekly 120 mg/kg infusions. 30,31 (CSL Behring, data on file). Furthermore, a pharmacokinetic model suggested a linear relationship between AAT dose and AAT serum levels within the concentrations investigated.…”
Section: Doctor Tim Greulichmentioning
confidence: 99%